2009
DOI: 10.1097/nmd.0b013e3181aac81b
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences, Anger Expression, and Cardiovascular Risk

Abstract: Research has established the influence of serum cholesterol and anger management style as cardiovascular risk factors. However, mixed and sometimes contradictory results have created uncertainty with respect to contributions of anger. Some incongruities may be accounted for on the basis of gender differences since a number of studies have employed male samples rather than female samples or mixed samples. The present study examined both gender and anger management style in relation to cardiovascular risk. One h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…No increased risk of the incidence of heart failure was observed among women with high, as compared to low, trait anger. This observation is consistent with the results of the few existing studies which have examined gender-specific effects of anger on the risk of cardiovascular disease 10, 17, 36, 37 . Results of those studies suggest a stronger harmful effect of anger on coronary heart disease events among men, as compared to women, perhaps reflecting the predominance of outward expression of anger among men (anger-out) and the extent to which this anger coping style may be associated with greater risk of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 91%
“…No increased risk of the incidence of heart failure was observed among women with high, as compared to low, trait anger. This observation is consistent with the results of the few existing studies which have examined gender-specific effects of anger on the risk of cardiovascular disease 10, 17, 36, 37 . Results of those studies suggest a stronger harmful effect of anger on coronary heart disease events among men, as compared to women, perhaps reflecting the predominance of outward expression of anger among men (anger-out) and the extent to which this anger coping style may be associated with greater risk of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 91%
“…186 Thus, economic, social, and physical environment factors appear to contribute to chronic negative psychological states, which may result in dysregulation of the autonomic nervous system 187 and associated increased blood pressure, greater adiposity, and insulin resistance (Biological Mechanisms section); increased likelihood of unhealthy behaviors (Behavioral Mechanisms section); additional chronic life stress [188][189][190][191][192][193][194][195][196] ; and the development and progression of CVD. Research in this area is continuing, [197][198][199][200] and inclusion of racial/ethnic and socioeconomically diverse populations in this research will be critical.…”
Section: Psychological Mechanismsmentioning
confidence: 99%
“…In addition, a handful of studies has documented sex differences in the degree to which anger regulation affects the physical health of patients (intrapersonal pathway; Doster, Purdum, Martin, Goven, & Moorefield, 2009; Hogan & Linden, 2005; Suarez, 2006) and their interpersonal function (Julkunen et al, 2009). Indeed, Julkunen and colleagues (2009) found that among female cancer patients, anger inhibition was related negatively to male spouse support, but male patients’ anger inhibition was not related significantly to female spouse support.…”
mentioning
confidence: 99%